2018
DOI: 10.1016/j.ymthe.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

miR-210 Enhances the Therapeutic Potential of Bone-Marrow-Derived Circulating Proangiogenic Cells in the Setting of Limb Ischemia

Abstract: Therapies based on circulating proangiogenic cells (PACs) have shown promise in ischemic disease models but require further optimization to reach the bedside. Ischemia-associated hypoxia robustly increases microRNA-210 (miR-210) expression in several cell types, including endothelial cells (ECs). In ECs, miR-210 represses EphrinA3 (EFNA3), inducing proangiogenic responses. This study provides new mechanistic evidences for a role of miR-210 in PACs. PACs were obtained from either adult peripheral blood or cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 71 publications
2
32
0
Order By: Relevance
“…These findings are in agreement with studies on the pro-angiogenic role of miR-210 observed in vitro [15,[31][32][33], as well as in miR-210 overexpression studies in mouse models of heart [20][21][22][23], limb [26], and brain ischemia [24,25,34]. Also concordant are studies showing that cord blood-derived cells expressing miR-210 display an increased potential in stimulating angiogenesis upon transplantation Taken together, these results indicate that miR-210 plays a pro-angiogenic role in vivo also in the absence of ischemic injury.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with studies on the pro-angiogenic role of miR-210 observed in vitro [15,[31][32][33], as well as in miR-210 overexpression studies in mouse models of heart [20][21][22][23], limb [26], and brain ischemia [24,25,34]. Also concordant are studies showing that cord blood-derived cells expressing miR-210 display an increased potential in stimulating angiogenesis upon transplantation Taken together, these results indicate that miR-210 plays a pro-angiogenic role in vivo also in the absence of ischemic injury.…”
Section: Discussionsupporting
confidence: 92%
“…In Vitro Angiogenesis BM-CD34 1 cells, their CCM, or isolated EVs were cocultured with HUVECs (1:1 ratio) on Matrigel (Corning Incorporated Life Sciences) (15).…”
Section: Immunostainingmentioning
confidence: 99%
“…microRNA (miR)-21 and miR-210 antagomirs were purchased from Ambion; Thermo Fisher Scientific, Inc. and the scrambled negative control (anti-miR-scr) was obtained from Shanghai GenePharma Co. Ltd. These antagomirs have been previously described and verified (13)(14)(15). Cells were transfected with 50 nM miR-21/-210 antagomir or 25 nM anti-miR-scr using RNAifectin™ (ABM, Inc.), according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%